A high step‐up DC‐DC converter based on three‐winding coupled inductor and voltage multiplier for renewable energy applications. Issue 6 (29th December 2022) - Luo, Peng; He, Jie; Ji, Huansheng; Li, Fuwei; Jiang, Haoyu; Shi, Limei; Chen, Guanghao
Abstract: A high step‐up DC‐DC converter for renewable energy applications is proposed. Based on a three‐winding coupled inductor and two voltage multiplier cells, the proposed converter obtains a high voltage conversion ratio. Through the passive clamp circuit, the voltage stress of the main switch is suppressed and the leakage energy of the coupled inductor is recycled. This leads to utilize a low on‐state power resistance and low voltage‐rating power switch that decreases the conduction losses. Meanwhile, the current stress of the diodes is minimized and the reverse recovery problem is alleviated. Thus, high efficiency can be achieved. Under continuous conduction mode (CCM) and discontinuous conduction mode (DCM), different operating principles and the mathematical derivations of the proposed converter are described in detail. To validate the feasibility of the proposed converter, a 320 W prototype with 25–38 V input voltage and 400 V output voltage is implemented. The measured maximum and full load efficiencies are 95.83 % and 94.96 %, respectively. Abstract : A high step‐up DC‐DC converter for renewable energy applications is proposed. Based on a three‐winding coupled inductor and two voltage multiplier cells, the proposed converter obtains a high voltage conversion ratio. Through the passive clamp circuit, the voltage stress of the main switch is suppressed and the leakage energy of the coupled inductor is recycled.